(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The issues with different approaches to teaching foreign languages in universities are discussed in the essay. The direct method, grammar-translation, audiovisual, audio-lingual, and communicative approaches all received special attention. Modern teaching methods, according to the author, involve the application of such a system of procedures, which are intended to help trainees master knowledge independently through active cognitive activity rather than to replicate the teacher’s ready-made knowledge presentations.